Solid electrolyte material and battery using same

By introducing specific element proportions and structures into the solid electrolyte material, the shortcomings of solid electrolyte materials in the prior art in terms of high-efficiency lithium ion conductivity and safety are solved, and the stable operation and high safety of lithium ion batteries are achieved under a temperature change environment.

JP7656876B2Active Publication Date: 2025-04-04PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022518613
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-30
Filing Date
2021-02-09
Publication Date
2025-04-04
Estimated Expiration
2041-02-09

AI Technical Summary

Technical Problem

In the prior art, solid electrolyte materials have a high sulfur content when conducting lithium ions efficiently, resulting in low safety and difficult to maintain lithium ion conductivity under temperature changing environments.

Method used

Solid electrolyte materials containing lithium (Li), steel (Ta) or tantalum (Nb), aluminum (Al), oxygen (O) and fluorine (F), chlorine (Cl) or bromine (Br) elements are used to improve lithium ion conductivity and reduce sulfur content by adjusting the proportion and structure of the elements.

Benefits of technology

It realizes efficient lithium-ion conductivity, ensures that the lithium-ion battery operates stably under temperature changing environments, and improves the battery safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656876000002
    Figure 0007656876000002
  • Figure 0007656876000003
    Figure 0007656876000003
  • Figure 0007656876000004
    Figure 0007656876000004
Patent Text Reader

Abstract

The solid electrolyte material according to the present invention contains Li, M, Al, O and X, wherein M is at least one element selected from the group consisting of Ta and Nb, and X is at least one element selected from the group consisting of F, Cl, and Br.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a solid electrolyte material and a battery using the same. [Background technology]

[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte material. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-129312 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a new, highly useful solid electrolyte material. [Means for solving the problem]

[0005] The solid electrolyte material of the present disclosure includes Li, M, Al, O, and X, where M is at least one selected from the group consisting of Ta and Nb, and X is at least one selected from the group consisting of F, Cl, and Br. Effect of the Invention

[0006] The present disclosure provides a highly useful new solid electrolyte material. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment. [Diagram 2] FIG. 2 shows a cross-sectional view of an electrode material 1100 according to a second embodiment. [Diagram 3]FIG. 3 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of a solid electrolyte material. [Figure 4A] FIG. 4A is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Examples 1 to 7. [Figure 4B] FIG. 4B is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Examples 8 and 9. [Diagram 5] FIG. 5 is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Comparative Examples 1 and 2. [Figure 6] FIG. 6 is a graph showing the initial discharge characteristics of the battery according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.

[0009] (First embodiment) The solid electrolyte material according to the first embodiment includes Li, M, Al, O, and X, where M is at least one selected from the group consisting of Ta and Nb, and X is at least one selected from the group consisting of F, Cl, and Br.

[0010] The solid electrolyte material according to the first embodiment can have, for example, a practical lithium ion conductivity, for example, a high lithium ion conductivity. Here, the high lithium ion conductivity is, for example, 1×10 -3 That is, the solid electrolyte material according to the first embodiment has a conductivity of, for example, 1×10 -3 It may have an ionic conductivity of mS / cm or more.

[0011] The solid electrolyte material according to the first embodiment can be used to obtain a battery having excellent charge / discharge characteristics. An example of the battery is an all-solid-state battery. The all-solid-state battery may be a primary battery or a secondary battery.

[0012] The solid electrolyte material according to the first embodiment can maintain high lithium ion conductivity in the expected temperature range of the battery. Therefore, the battery using the solid electrolyte material according to the first embodiment can operate stably even in an environment with temperature changes. The temperature range of the battery is, for example, from -30°C to 80°C.

[0013] It is desirable that the solid electrolyte material according to the first embodiment does not substantially contain sulfur. The solid electrolyte material according to the first embodiment does not substantially contain sulfur means that the solid electrolyte material does not contain sulfur as a constituent element, except for sulfur that is inevitably mixed in as an impurity. In this case, the amount of sulfur mixed in the solid electrolyte material as an impurity is, for example, 1 mol % or less. It is desirable that the solid electrolyte material according to the first embodiment does not contain sulfur. A solid electrolyte material that does not contain sulfur is excellent in safety because hydrogen sulfide is not generated even when exposed to the atmosphere. The sulfide solid electrolyte material disclosed in Patent Document 1 may generate hydrogen sulfide when exposed to the atmosphere.

[0014] In order to enhance the ionic conductivity of the solid electrolyte material, the solid electrolyte material according to the first embodiment may be substantially composed of Li, M, Al, O, and X. Here, "the solid electrolyte material according to the first embodiment is substantially composed of Li, M, Al, O, and X" means that the ratio (i.e., the molar fraction) of the total amount of substance of Li, M, Al, O, and X to the total amount of substance of all elements constituting the solid electrolyte material according to the first embodiment is 90% or more. As an example, the ratio may be 95% or more. The solid electrolyte material according to the first embodiment may be composed only of Li, M, Al, O, and X.

[0015] The solid electrolyte material according to the first embodiment may have a diffraction peak in the range of diffraction angles 2θ of 11.08° or more and 15.63° or less (hereinafter referred to as the "first range") in the X-ray diffraction pattern. In such a solid electrolyte material, a path for lithium ion diffusion is easily formed. As a result, the solid electrolyte material according to the first embodiment has high lithium ion conductivity.

[0016] A diffraction peak in an X-ray diffraction pattern is also simply called a "peak."

[0017] The X-ray diffraction pattern of the solid electrolyte material according to the first embodiment can be obtained by X-ray diffraction measurement by the θ-2θ method using Cu-Kα radiation (wavelengths of 1.5405 Å and 1.5444 Å, ie, wavelengths of 0.15405 nm and 0.15444 nm).

[0018] The peak angle is the angle that indicates the maximum intensity of the mountain-shaped part where the S / N ratio is 3 or more and the half-width is 10° or less. The half-width is the maximum intensity of the peak. MAX When the intensity is I MAX The signal-to-noise ratio (SN ratio) is the ratio of the signal (S) to the background noise (N).

[0019] In order to enhance the ionic conductivity of the solid electrolyte material, X may be at least one selected from the group consisting of Cl and Br.

[0020] To enhance the ionic conductivity of the solid electrolyte, M may be Ta.

[0021] In order to increase the ionic conductivity of the solid electrolyte material, the ratio of the amount of substance of Al to the sum of the amounts of substances of M and Al may be 5% or more and 70% or less. The ratio of the amount of substance of Al to the sum of the amounts of substances of M and Al is calculated by the formula: {(amount of substance of Al) / (amount of substance of M+amount of substance of Al)}×100. Hereinafter, the ratio of the amount of substance of Al to the sum of the amounts of substances of M and Al is also referred to as the "Al / (M+Al) molar ratio."

[0022] In order to enhance the ionic conductivity of the solid electrolyte material, the Al / (M+Al) molar ratio may be 10% or more and 70% or less.

[0023] In order to enhance the ionic conductivity of the solid electrolyte material, the Al / (M+Al) molar ratio may be 10% or more and 60% or less.

[0024] To further increase the ionic conductivity of the solid electrolyte material, the Al / (M+Al) molar ratio may be 10% or more and 40% or less.

[0025] The shape of the solid electrolyte material according to the first embodiment is not limited. Examples of the shape are needle-like, spherical, and elliptical. The solid electrolyte material according to the first embodiment may be in the form of particles. The solid electrolyte material according to the first embodiment may be formed to have a pellet or plate shape.

[0026] When the solid electrolyte material according to the first embodiment has a particulate shape (for example, a spherical shape), the solid electrolyte material may have a median diameter of 0.1 μm or more and 100 μm or less, or may have a median diameter of 0.5 μm or more and 10 μm or less. This allows the solid electrolyte material according to the first embodiment and other materials to be dispersed well. The median diameter of the particles means a particle diameter (d50) corresponding to a volume cumulative 50% in a volume-based particle size distribution. The volume-based particle size distribution can be measured by a laser diffraction measurement device or an image analysis device.

[0027] <Method of manufacturing solid electrolyte material> The solid electrolyte material according to the first embodiment can be produced by the following method.

[0028] Raw material powders are prepared and mixed to have a desired composition, examples of which include oxides, hydroxides, halides, or oxyhalides.

[0029] As an example, when the solid electrolyte material is composed of Li, Ta, Al, O, and Cl, and the Al / (M+Al) molar ratio at the time of mixing the raw materials is 10%, i.e., M is Ta, X is Cl, and the Al / (M+Al) molar ratio at the time of mixing the raw materials is 10%, Li2O2, TaCl5, and AlCl3 are mixed as raw material powders in a Li2O2:TaCl5:AlCl3 molar ratio of 1:1.8:0.2. M and X are determined by the selection of the raw material powders. The Al / (M+Al) molar ratio is determined by the selection of the molar ratio of the raw material powders. The raw material powders may be mixed in a pre-adjusted molar ratio to offset composition changes that may occur in the synthesis process.

[0030] A mixture of raw material powders is reacted mechanochemically with each other in a mixing device such as a planetary ball mill to obtain a reactant. This method is often called mechanochemical milling. The reactant may be sintered in a vacuum or in an inert atmosphere. Alternatively, the mixture may be sintered in a vacuum or in an inert gas atmosphere to obtain a reactant. By these methods, a solid electrolyte material according to the first embodiment is obtained. The inert atmosphere is, for example, an argon atmosphere or a nitrogen atmosphere.

[0031] By selecting the raw material powders, the mixing ratio of the raw material powders, and the reaction conditions, the peak position of the solid electrolyte material according to the first embodiment, that is, the crystal phase configuration, can be adjusted to a desired one.

[0032] The composition of the solid electrolyte material can be determined, for example, by inductively coupled plasma optical emission spectroscopy or ion chromatography. For example, the compositions of Li, M, and Al can be determined by inductively coupled plasma optical emission spectroscopy, and the composition of X can be determined by ion chromatography.

[0033] Second embodiment The second embodiment will be described below. The matters described in the first embodiment will be omitted as appropriate.

[0034] The battery according to the second embodiment includes a positive electrode, an electrolyte layer, and a negative electrode. The electrolyte layer is disposed between the positive electrode and the negative electrode. At least one selected from the group consisting of the positive electrode, the electrolyte layer, and the negative electrode contains the solid electrolyte material according to the first embodiment.

[0035] The battery according to the second embodiment has excellent charge / discharge characteristics since it contains the solid electrolyte material according to the first embodiment.

[0036] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment.

[0037] The battery 1000 includes a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203.

[0038] The positive electrode 201 contains positive electrode active material particles 204 and solid electrolyte particles 100 .

[0039] The electrolyte layer 202 contains an electrolyte material, for example, a solid electrolyte material.

[0040] The negative electrode 203 contains negative electrode active material particles 205 and solid electrolyte particles 100 .

[0041] The solid electrolyte particle 100 is a particle containing the solid electrolyte material according to the first embodiment. The solid electrolyte particle 100 may be a particle containing the solid electrolyte material according to the first embodiment as a main component. The particle containing the solid electrolyte material according to the first embodiment as a main component means a particle in which the component contained most abundantly in terms of molar ratio is the solid electrolyte material according to the first embodiment. The solid electrolyte particle 100 may be a particle made of the solid electrolyte material according to the first embodiment.

[0042] The positive electrode 201 contains a material capable of absorbing and releasing metal ions such as lithium ions. The material is, for example, a positive electrode active material (for example, positive electrode active material particles 204).

[0043] Examples of the positive electrode active material include lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, or transition metal oxynitrides. Examples of the lithium-containing transition metal oxides include Li(Ni,Co,Al)O2, Li(Ni,Co,Mn)O2, or LiCoO2. From the viewpoints of the cost and safety of the battery, lithium phosphate may be used as the positive electrode active material.

[0044] In the present disclosure, “(A,B,C)” means “at least one selected from the group consisting of A, B, and C”.

[0045] The positive electrode 201 may contain not only the solid electrolyte material according to the first embodiment but also a transition metal oxyfluoride as the positive electrode active material. Even if the solid electrolyte material according to the first embodiment is fluorinated by a transition metal fluoride, it is difficult to form a resistance layer. As a result, the battery has high charge and discharge efficiency.

[0046] The transition metal oxyfluoride contains oxygen and fluorine. As an example, the transition metal oxyfluoride may be a compound represented by the composition formula Li p Me q O m F n Here, Me is at least one selected from the group consisting of Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, and P, and the following mathematical formulas: 0.5 ≦ p ≦ 1.5, 0.5 ≦ q ≦ 1.0, 1 ≦ m < 2, and 0 < n ≦ 1 are satisfied. An example of such a transition metal oxyfluoride is Li 1.05 (Ni 0.35 Co 0.35 Mn 0.3 ) 0.95 O 1.9 F 0.1 .

[0047] The positive electrode active material particles 204 may have a median diameter of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median diameter of 0.1 μm or more, the positive electrode active material particles 204 and the solid electrolyte particles 100 can be well dispersed in the positive electrode 201. This improves the charge / discharge characteristics of the battery. When the positive electrode active material particles 204 have a median diameter of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 improves. This allows the battery to operate at high power.

[0048] The positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100. This allows the positive electrode active material particles 204 and the solid electrolyte particles 100 to be dispersed well.

[0049] To increase the energy density and output of the battery, in the positive electrode 201, the ratio of the volume of the positive electrode active material particles 204 to the sum of the volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0050] 2 shows a cross-sectional view of an electrode material 1100 according to a second embodiment. The electrode material 1100 is included in, for example, a positive electrode 201. A coating layer 216 may be formed on the surface of the electrode active material particle 206 in order to prevent the electrode active material particle 206 (i.e., the positive electrode active material) from reacting with the solid electrolyte particle 100. This makes it possible to suppress an increase in the reaction overvoltage of the battery. Examples of coating materials included in the coating layer 216 include a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte.

[0051] When the solid electrolyte particle 100 is a sulfide solid electrolyte, the coating material may be the solid electrolyte material according to the first embodiment. The solid electrolyte material according to the first embodiment is less susceptible to oxidation than the sulfide solid electrolyte, and therefore can suppress an increase in the reaction overvoltage of the battery.

[0052] To increase the energy density and power output of the battery, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.

[0053] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. The electrolyte layer 202 may be a solid electrolyte layer.

[0054] The electrolyte layer 202 may contain the solid electrolyte material according to the first embodiment. The electrolyte layer 202 may be made of only the solid electrolyte material according to the first embodiment.

[0055] The solid electrolyte material contained in the electrolyte layer 202 may be composed only of a solid electrolyte material different from the solid electrolyte material according to the first embodiment. Examples of the solid electrolyte material different from the solid electrolyte material according to the first embodiment include Li2MgX'4, Li2FeX'4, Li(Al,Ga,In)X'4, Li3(Al,Ga,In)X'6, or LiI, where X' is at least one selected from the group consisting of F, Cl, Br, and I.

[0056] Hereinafter, the solid electrolyte material according to the first embodiment will be referred to as a first solid electrolyte material, and a solid electrolyte material different from the solid electrolyte material according to the first embodiment will be referred to as a second solid electrolyte material.

[0057] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed. A layer made of the first solid electrolyte material and a layer made of the second solid electrolyte material may be stacked along the stacking direction of the battery 1000.

[0058] The electrolyte layer 202 may have a thickness of 1 μm or more and 100 μm or less. When the electrolyte layer 202 has a thickness of 1 μm or more, the positive electrode 201 and the negative electrode 203 are less likely to short-circuit. When the electrolyte layer 202 has a thickness of 100 μm or less, the battery can operate at high power.

[0059] Another electrolyte layer may be further provided between the electrolyte layer 202 and the negative electrode 203. That is, a second electrolyte layer may be further provided between the electrolyte layer 202 and the negative electrode 203. For example, when the electrolyte layer 202 contains a first solid electrolyte material, the second electrolyte layer may be composed of another solid electrolyte material that is electrochemically more stable than the first solid electrolyte material. Specifically, the reduction potential of the solid electrolyte material constituting the second electrolyte layer may be lower than the reduction potential of the first solid electrolyte material. This allows the first solid electrolyte material to be used without being reduced, and the high ionic conductivity of the first solid electrolyte material can be more stably maintained. As a result, the charge / discharge efficiency of the battery can be improved.

[0060] The negative electrode 203 contains a material capable of absorbing and releasing metal ions (for example, lithium ions). The material is, for example, a negative electrode active material (for example, negative electrode active material particles 205).

[0061] Examples of the negative electrode active material are metal materials, carbon materials, oxides, nitrides, tin compounds, or silicon compounds. The metal material may be a single metal or an alloy. Examples of the metal material are lithium metal or a lithium alloy. Examples of the carbon material are natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, suitable examples of the negative electrode active material are silicon (Si), tin (Sn), silicon compounds, or tin compounds.

[0062] The negative electrode active material may be selected based on the reduction resistance of the solid electrolyte material contained in the negative electrode 203. When the negative electrode 203 contains a first solid electrolyte material, a material capable of absorbing and releasing lithium ions at 0.27 V or more relative to lithium may be used as the negative electrode active material. If the negative electrode active material is such a material, it is possible to suppress the reduction of the first solid electrolyte material contained in the negative electrode 203. As a result, the battery has high charge and discharge efficiency. Examples of the negative electrode active material are titanium oxide, indium metal, or lithium alloy. An example of titanium oxide is Li4Ti5O 12 , LiTi2O4, or TiO2.

[0063] The negative electrode active material particles 205 may have a median diameter of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median diameter of 0.1 μm or more, the negative electrode active material particles 205 and the solid electrolyte particles 100 can be well dispersed in the negative electrode 203. This improves the charge / discharge characteristics of the battery. When the negative electrode active material particles 205 have a median diameter of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 improves. This allows the battery to operate at high power.

[0064] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. This allows the negative electrode active material particles 205 and the solid electrolyte particles 100 to be dispersed well.

[0065] In order to increase the energy density and output of the battery, in the negative electrode 203, the ratio of the volume of the negative electrode active material particles 205 to the sum of the volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0066] 2 is included in the negative electrode 203, for example. A coating layer 216 may be formed on the surface of the electrode active material particle 206 to prevent the electrode active material particle 206 (i.e., the negative electrode active material) from reacting with the solid electrolyte particle 100. This allows the battery to have high charge / discharge efficiency. Examples of the coating material included in the coating layer 216 include a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, or a halide solid electrolyte.

[0067] When the solid electrolyte particle 100 is the first solid electrolyte material, the coating material may include a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer solid electrolyte. An example of a sulfide solid electrolyte is Li2S-P2S5. An example of an oxide solid electrolyte is trilithium phosphate. An example of a polymer solid electrolyte is a composite compound of polyethylene oxide and a lithium salt. An example of such a polymer solid electrolyte is lithium bis(trifluoromethanesulfonyl)imide.

[0068] To increase the energy density and power output of the battery, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.

[0069] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second solid electrolyte material for the purpose of increasing ion conductivity. Examples of the second solid electrolyte material include a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, or an organic polymer solid electrolyte.

[0070] In the present disclosure, a "sulfide solid electrolyte" refers to a solid electrolyte containing sulfur. An "oxide solid electrolyte" refers to a solid electrolyte containing oxygen. The oxide solid electrolyte may contain anions other than oxygen (excluding sulfur anions and halogen anions). A "halide solid electrolyte" refers to a solid electrolyte that contains a halogen element and is substantially free of sulfur. The halide solid electrolyte may contain not only a halogen element but also oxygen.

[0071] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 It is.

[0072] Examples of oxide solid electrolytes include: (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or elemental substitutions thereof; (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3; (iii) Li 14 ZnGeO 16 LISICON-type solid electrolytes such as Li4SiO4, LiGeO4 or elemental substitutes thereof; (iv) Li7La3Zr2O 12or a garnet-type solid electrolyte such as an elemental substitution product thereof; or (v) Li3PO4 or its N-substituted derivatives It is.

[0073] An example of a halide solid electrolyte is Li a Me' b Y c Z6, where the formula: a+mb+3c=6, and c>0 is satisfied. Me' is at least one selected from the group consisting of metal elements and metalloid elements other than Li and Y. Z is at least one selected from the group consisting of F, Cl, Br, and I. The value of m represents the valence of Me'.

[0074] The "metalloid elements" are B, Si, Ge, As, Sb, and Te.

[0075] "Metal elements" refers to all elements in groups 1 to 12 of the periodic table (excluding hydrogen) and all elements in groups 13 to 16 of the periodic table (excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se).

[0076] In order to increase the ionic conductivity of the halide solid electrolyte, Me' may be at least one selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb.

[0077] Examples of halide solid electrolytes are Li3YCl6 or Li3YBr6.

[0078] When the electrolyte layer 202 contains the first solid electrolyte material, the negative electrode 203 may contain a sulfide solid electrolyte. This allows the sulfide solid electrolyte, which is electrochemically stable with respect to the negative electrode active material, to prevent the first solid electrolyte material and the negative electrode active material from contacting each other. As a result, the battery has low internal resistance.

[0079] An example of the organic polymer solid electrolyte is a compound of a polymer compound and a lithium salt. The polymer compound may have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt, and therefore has a higher ionic conductivity.

[0080] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.

[0081] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a nonaqueous electrolyte, a gel electrolyte, or an ionic liquid for the purpose of facilitating the exchange of lithium ions and improving the output characteristics of the battery.

[0082] The non-aqueous electrolyte includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent are a cyclic carbonate ester solvent, a chain carbonate ester solvent, a cyclic ether solvent, a chain ether solvent, a cyclic ester solvent, a chain ester solvent, or a fluorine solvent. Examples of the cyclic carbonate ester solvent are ethylene carbonate, propylene carbonate, or butylene carbonate. Examples of the chain carbonate ester solvent are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of the cyclic ether solvent are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane. Examples of the chain ether solvent are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of the cyclic ester solvent are γ-butyrolactone. Examples of the chain ester solvent are methyl acetate. Examples of fluorine-containing solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, or fluorodimethylene carbonate. One non-aqueous solvent selected from these may be used alone. Alternatively, a mixture of two or more non-aqueous solvents selected from these may be used.

[0083] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One type of lithium salt selected from these may be used alone. Alternatively, a mixture of two or more types of lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 mol / liter to 2 mol / liter.

[0084] The gel electrolyte may be a polymer material impregnated with a non-aqueous electrolyte, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0085] Examples of cations contained in ionic liquids are: (i) Aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium salts, (ii) aliphatic cyclic ammonium such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, or piperidiniums, or (iii) nitrogen-containing heterocyclic aromatic cations such as pyridiniums or imidazoliums It is.

[0086] An example of an anion contained in an ionic liquid is PF6 - , BF4 - , SbF6 - , AsF6 - , SO3CF3 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - It is.

[0087] The ionic liquid may contain a lithium salt.

[0088] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder in order to increase adhesion between particles.

[0089] Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, and carboxymethylcellulose. A copolymer may be used as the binder. An example of the binder is a copolymer of two or more materials selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. A mixture of two or more materials selected from the above materials may be used.

[0090] At least one selected from the group consisting of the positive electrode 201 and the negative electrode 203 may contain a conductive assistant to enhance electronic conductivity.

[0091] Examples of the conductive additive include: (i) Graphites, such as natural or synthetic graphite; (ii) Carbon blacks such as acetylene black or ketjen black; (iii) conductive fibers, such as carbon or metal fibers; (iv) fluorocarbons, (v) Metal powders such as aluminum; (vi) conductive whiskers such as zinc oxide or potassium titanate; (vii) a conductive metal oxide, such as titanium dioxide; or (viii) Conductive polymers such as polyaniline, polypyrrole, or polythiophene In order to reduce costs, the above-mentioned conductive assistant (i) or (ii) may be used.

[0092] Examples of the shape of the battery according to the second embodiment are a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, or a laminate type.

[0093] The battery according to the second embodiment may be manufactured, for example, by preparing a material for forming a positive electrode, a material for forming an electrolyte layer, and a material for forming a negative electrode, and producing a laminate in which the positive electrode, the electrolyte layer, and the negative electrode are arranged in this order by a known method. EXAMPLES

[0094] Hereinafter, the present disclosure will be described in more detail using examples.

[0095] Example 1 [Preparation of solid electrolyte materials] In a dry atmosphere having a dew point of -30°C or less (hereinafter referred to as "dry atmosphere"), Li2O2, TaCl5, and AlCl3 were prepared as raw material powders in a molar ratio of Li2O2:TaCl5:AlCl3 of 1:1.8:0.2. These materials were ground and mixed in a mortar to obtain a mixture. The obtained mixture was milled at 600 rpm for 24 hours using a planetary ball mill (Fritsch, P-7 type). In this manner, a powder of the solid electrolyte material according to Example 1 was obtained.

[0096] [Evaluation of ionic conductivity] FIG. 3 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of a solid electrolyte material.

[0097] The pressure molding die 300 had an upper punch 301, a frame 302, and a lower punch 303. The frame 302 was made of insulating polycarbonate. Both the upper punch 301 and the lower punch 303 were made of electronically conductive stainless steel.

[0098] Using the pressure molding die 300 shown in FIG. 3, the ionic conductivity of the solid electrolyte material according to Example 1 was measured by the following method.

[0099] In a dry atmosphere, the powder of the solid electrolyte material according to Example 1 was filled into the inside of a pressure molding die 300. Inside the pressure molding die 300, a pressure of 300 MPa was applied to the solid electrolyte material according to Example 1 (i.e., the powder of the solid electrolyte material 101 in FIG. 3 ) using an upper punch 301 and a lower punch 303.

[0100] While the pressure was still applied, the upper punch 301 and the lower punch 303 were connected to a potentiostat (VersaSTAT4, manufactured by Princeton Applied Research) equipped with a frequency response analyzer. The upper punch 301 was connected to a working electrode and a terminal for measuring potential. The lower punch 303 was connected to a counter electrode and a reference electrode. The ionic conductivity of the solid electrolyte material according to Example 1 was measured at room temperature by electrochemical impedance measurement. As a result, the ionic conductivity measured at 22°C was 4.2 mS / cm.

[0101] [X-ray diffraction measurement] 4A is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Examples 1 to 7. The X-ray diffraction patterns were measured by the following method.

[0102] The X-ray diffraction pattern of the solid electrolyte material according to Example 1 was measured using an X-ray diffractometer (MiniFlex600, manufactured by RIGAKU) in a dry atmosphere having a dew point of -45°C or less. Cu-Kα radiation (wavelengths 1.5405 Å and 1.5444 Å) was used as the X-ray source.

[0103] The solid electrolyte material of Example 1 had a peak at 12.50°.

[0104] [Battery construction] In an argon atmosphere having a dew point of -60°C or less, the solid electrolyte material according to Example 1 and the positive electrode active material LiCoO2 were prepared in a volume ratio of 50:50. These materials were mixed in a mortar to obtain a positive electrode mixture.

[0105] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material (120 mg) according to Example 1 and the above-mentioned positive electrode mixture (10.6 mg) were laminated to obtain a laminate. A pressure of 360 MPa was applied to this laminate to form a solid electrolyte layer and a positive electrode. The solid electrolyte layer had a thickness of 500 μm.

[0106] Next, a Li-In alloy having a thickness of 200 μm was laminated on the solid electrolyte layer, and a pressure of 80 MPa was applied to this laminate to form a negative electrode.

[0107] Current collectors formed from stainless steel were attached to the positive and negative electrodes, and current collecting leads were attached to the current collectors.

[0108] Finally, the inside of the insulating tube was isolated from the outside atmosphere using an insulating ferrule, and the inside of the tube was sealed.

[0109] In this manner, the battery according to Example 1 was obtained.

[0110] [Charge / discharge test] 6 is a graph showing the initial discharge characteristics of the battery according to Example 1. The initial discharge characteristics were measured by the following method.

[0111] The battery according to Example 1 was placed in a thermostatic chamber at 25°C.

[0112] The battery according to Example 1 was charged at a current value of 56 μA until a voltage of 3.6 V was reached, the current density corresponding to a 0.05 C rate.

[0113] The cell was then discharged at a current of 56 μA until a voltage of 1.9 V was reached.

[0114] The battery according to Example 1 was charged and discharged at room temperature.

[0115] As a result of the charge / discharge test, the battery according to Example 1 had an initial discharge capacity of 1.06 mAh.

[0116] (Examples 2 to 9 and Comparative Examples 1 to 2) [Preparation of solid electrolyte materials] In Example 2, Li2O2, TaCl5, and AlCl3 were prepared as raw material powders with a Li2O2:TaCl5:AlCl3 molar ratio of 1:1.8:0.2. The mixture was milled and then calcined at 200°C for 3 hours.

[0117] In Example 3, Li2O2, TaCl5, and AlCl3 were prepared as raw material powders in a Li2O2:TaCl5:AlCl3 molar ratio of 1:1.2:0.8.

[0118] In Example 4, Li2O2, TaCl5, and AlCl3 were prepared as raw material powders with a molar ratio of Li2O2:TaCl5:AlCl3 of 1:1.2:0.8. The mixture was milled and then calcined at 200°C for 3 hours.

[0119] In Example 5, Li2O2, TaCl5, and AlCl3 were prepared as raw material powders in a Li2O2:TaCl5:AlCl3 molar ratio of 1:0.8:1.2.

[0120] In Example 6, Li2O2, TaCl5, and AlCl3 were prepared as raw material powders with a Li2O2:TaCl5:AlCl3 molar ratio of 1:0.8:1.2. The mixture was milled and then calcined at 200°C for 3 hours.

[0121] In Example 7, raw powders of Li2O2, TaCl5, AlCl3, and TaF5 were prepared in a molar ratio of Li2O2:TaCl5:AlCl3:TaF5 of 1:1.7:0.2:0.1. The mixture was milled and then calcined at 200°C for 3 hours.

[0122] In Example 8, Li2O2, NbCl5, and AlCl3 were prepared as raw material powders in a Li2O2:NbCl5:AlCl3 molar ratio of 1:1.2:0.8.

[0123] In Example 9, Li2O2, NbCl5, and AlCl3 were prepared as raw powders with a Li2O2:NbCl5:AlCl3 molar ratio of 1:1.2:0.8. The mixture was milled and then calcined at 80°C for 3 hours.

[0124] In Comparative Example 1, Li2O2 and LiCl were prepared as raw material powders so that the molar ratio of Li2O2:LiCl was 1:1.

[0125] In Comparative Example 2, LiCl and TaCl5 were prepared as raw material powders so that the LiCl:TaCl5 molar ratio was 1:1.

[0126] Except for the above, the solid electrolyte materials according to Examples 2 to 9 and Comparative Examples 1 and 2 were obtained in the same manner as in Example 1.

[0127] [Evaluation of ionic conductivity] The ionic conductivities of the solid electrolyte materials according to Examples 2 to 9, Comparative Example 1, and Comparative Example 2 were measured in the same manner as in Example 1. The measurement results are shown in Table 1.

[0128] [X-ray diffraction] The X-ray diffraction patterns of the solid electrolyte materials according to Examples 2 to 9, Comparative Example 1, and Comparative Example 2 were measured in the same manner as in Example 1. FIG. 4A is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Examples 1 to 7. FIG. 4B is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Examples 8 and 9. FIG. 5 is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Comparative Examples 1 and 2.

[0129] The solid electrolyte material according to Example 2 had a peak at 11.13°.

[0130] The solid electrolyte material according to Example 3 had a peak at 12.52°.

[0131] The solid electrolyte material according to Example 4 had a peak at 15.53°.

[0132] The solid electrolyte material according to Example 5 did not have a peak in the first range.

[0133] The solid electrolyte material according to Example 6 had a peak at 15.55°.

[0134] The solid electrolyte material of Example 7 had a peak at 11.15°.

[0135] The solid electrolyte material of Example 8 had a peak at 14.29°.

[0136] The solid electrolyte material of Example 9 had a peak at 13.84°.

[0137] Comparative Example 1 and Comparative Example 2 did not have a peak in the first range.

[0138] [Table 1]

[0139] (Consideration) As is clear from Table 1, the solid electrolyte materials according to Examples 1 to 9 have a melting point of 1×10 -3 It has a high ionic conductivity of more than 1×10 -2 It has high ionic conductivity of more than mS / cm.

[0140] As is clear from a comparison of Examples 1 to 4 with Examples 5 and 6, when the ratio of the amount of Al to the total amount of M and Al is 10% or more and 40% or less, the ionic conductivity of the solid electrolyte material is further increased.

[0141] As is clear from a comparison of Examples 3 and 4 with Examples 8 and 9, the ionic conductivity of the solid electrolyte material is higher when M is Ta than when M is Nb.

[0142] The solid electrolyte materials according to Examples 1 to 9 do not contain sulfur and therefore do not generate hydrogen sulfide.

[0143] As described above, the solid electrolyte material according to the present disclosure has a practical lithium ion conductivity and is therefore suitable for providing a battery having excellent charge / discharge characteristics. [Industrial Applicability]

[0144] The battery of the present disclosure is used, for example, in an all-solid-state lithium ion secondary battery.

Claims

1. A solid electrolyte material consisting essentially of Li, M, Al, O, and X, M is at least one selected from the group consisting of Ta and Nb; X is at least one selected from the group consisting of F, Cl, and Br; The ratio of the total amount of substance of Li, M, Al, O, and X to the total amount of substance of all elements constituting the solid electrolyte material is 95% or more; Solid electrolyte material.

2. In an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation, the crystal phase has a peak in the range of diffraction angle 2θ of 11.08° or more and 15.63° or less. The solid electrolyte material according to claim 1 .

3. X is at least one selected from the group consisting of Cl and Br; The solid electrolyte material according to claim 1 or 2.

4. M is Ta; The solid electrolyte material according to claim 1 .

5. The ratio of the amount of substance of Al to the total amount of substances of M and Al is 5% or more and 70% or less. The solid electrolyte material according to claim 1 .

6. The ratio of the amount of substance of Al to the total amount of substances of M and Al is 10% or more and 70% or less. The solid electrolyte material according to claim 5 .

7. The ratio of the amount of substance of Al to the total amount of substances of M and Al is 10% or more and 60% or less. The solid electrolyte material according to claim 6.

8. positive electrode, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode; Equipped with At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 7. battery.

Citation Information

Patent Citations

  • Mg2+, Al3+, Zr4+ and F- ion co-doped garnet-type solid electrolyte

    CN102780031A

  • Oxide solid electrolytes based on lithium halide-doping and low-temperature sintering method thereof

    CN107732295A

  • Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery

    JP2011129312A

  • Composite solid electrolyte

    JP2017107665A

  • Positive electrode material and lithium secondary battery using the same

    JP2019057450A